Comparison of Local and Spinal Anesthesia for Inguinal Hernia Repair - Bunlue Chowdok; Araya Khaimook (Journal of Health Science and Medical Research (JHSMR), 2010)
Inguinal hernial repair is one of the most common surgical procedures in a general surgical practice. The usual anesthetic methods for elective inguinal herniorrhaphy are spinal or local anesthesia. Local anesthesia is very safe for patients with high cardiovascular risk. However, the usage of local anesthesia is not widely accepted in Thailand. We conducted a prospective randomized controlled trial in 60 adult patients to compare local anesthesia with conventional spinal anesthesia for electiveunilateral inguinal hernia repair. The results showed that total time spent in operative room, pain scores at 24 hours after operation, and length of hospital stay for patients randomized to receivelocal anesthesia were significantly less than in patients randomized to receive spinal anesthesia. In conclusion, local anesthesia as an anesthetic method for inguinal repair can be performed successfully. This choice of anesthesia helps avoiding risks from spinal anesthesia. The only complication in the local anesthesia group was one postoperative wound hematoma. There was no urinary retention in patients receiving local anesthesia.